2004
DOI: 10.1016/j.jacc.2004.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial and epicardial radiofrequency ablation of ventricular tachycardia associated with dilated cardiomyopathy

Abstract: The VTs in DCM are most commonly the result of myocardial re-entry associated with scar. Scars are often adjacent to a valve annulus, deep in the endocardium, and can be greater in extent on the epicardium than on the endocardium. The use of epicardial mapping and radiofrequency is likely to improve success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
300
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(318 citation statements)
references
References 23 publications
10
300
2
6
Order By: Relevance
“…Both endocardial or epicardial diseased substrates in NICM could exist and contain critical isthmuses for a successful ablation 53. These abnormal substrates frequently harbor fibrotic and scar tissue that lead to slow conduction and fractionated electrograms in human tissue experiments 54.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…Both endocardial or epicardial diseased substrates in NICM could exist and contain critical isthmuses for a successful ablation 53. These abnormal substrates frequently harbor fibrotic and scar tissue that lead to slow conduction and fractionated electrograms in human tissue experiments 54.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…NIDCM is known to have increased risk of VT, the substrate of monomorphic VT in NIDCM often exists in the deep endocardium 2 or adjacent to a valve annulus on both the epicardium and endocardium. [1][2][3][4] Haqqani et al reported that the isolated septal substrate in patients with NIDCM was rare and only 11.6% of these patients. 5 Although we tried to demonstrate the concealed entrainment at the initial strategy, the VT did not sustain long enough to perform such diagnostic maneuvers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The major substrates for VT in patients with NIDCM have been reported to be the basal periannular region of the left ventricle (LV). [1][2][3][4] On the other hand, isolated septal substrate is reported to be rare, and found in only 10% of these patients. 5 In addition, the treatment of VT associated with the septal substrate is challenging because the scar area exists entirely intramural zone or there are multiple VT circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging with delayed gadolinium-enhancement and voltage mapping demonstrates that scars are often located adjacent to a valve annulus [36,37]. These features likely account for the general perception that patients present with multiple morphologies of VT, and ablation is more difficult than that in the remote MI-VT population.…”
Section: Non-ischemic Dilated Cardiomyopathymentioning
confidence: 99%